Avaliação econômica-financeira para a implantação de uma subunidade de álcool de segunda geração na indústria sucroalcooleira - Alcantra, Christina do Vale Pena (2017)
Sugarcane bagasse and straw, which were previously evaluated as waste without function, are shown as a source to supply the power needs of the plants, through the cogeneration of electric energy, both for self-sufficiency and for the sale to the concessionaire. Energy, and can be used for the production of 2G ethanol, and thus play an important role for the mills, because it has a source of more revenue. Therefore, it is possible to increase ethanol production only through the use of sugarcane straw and bagasse, without expanding the planted area, contributing to the increase and productivity in the sector. In this context, the objective of this work is to analyze the costs of the production of 2G ethanol, based on the evaluation of the technical-economic viability for the implementation of a second generation alcohol production unit from the sugar cane residues. The evaluation of the economic-financial performance is not a recent practice in organizations, and it is from the analysis of the indicators used (Contribution Margin, IRR, NPV and Discounted Payback) that the performance evaluation of the six sugar factories in the State of Espirito Santo, through four distinct scenarios: Scenario I - Production of 2G alcohol from the straw obtained in the sugarcane-producing areas of the capixabas municipalities; Scenario II - Production of 2G alcohol from the use of all sugarcane bagasse originated in the plant itself and without cogeneration of electric energy; Scenario III - Production of 2G alcohol through the use of the bagasse surplus from the plant itself; And Scenario IV - Production of 2G alcohol from the bagasse surplus acquired by the purchase of this waste in the other Espirito Santo plants. In order to assess the economic feasibility of this implementation, in the various scenarios, it is considered necessary an initial investment to purchase equipment (reactors for pre-treatment and hydrolysis). The other stages of 2G ethanol production, fermentation and distillation, are identical to 1G ethanol, so these processes will be carried out in the existing plant with its own machinery.